Upcycling Milk Industry Byproducts into Tenebrio molitor Larvae: Investigation on Fat, Protein, and Sugar Composition - Annalaura Brai; Cassia Neri; Franca Tarchi; Federica Poggialini; Chiara Vagaggini; Riccardo Frosinini; Sauro Simoni; Valeria Francardi; Elena Dreassi (Foods)
Edible insects represent a growing sector of the food industry and have a low carbon footprint. Noteworthy, insects can upcycle different leftovers and byproducts into high-quality nutrients. Herein, the larvae of the edible insect Tenebrio molitor (TML) were fed using local milk industry byproducts. Mozzarella whey and whey permeate obtained in cheese production were used to formulate three alternative diets. Both byproducts are rich in sugars, in particular the disaccharide lactose and the monosaccharides glucose and galactose. Two of the three diets did not interfere with biometric data and vitality, while the use of whey permeate alone significantly reduced development. At the end of the trial, the proximate composition of TML was strongly affected, with an increased protein content of up to +7% and a favorable fat composition. The analysis of secondary metabolites revealed the accumulation of different compounds, in particular monounsaturated fatty acids (MUFAs), amino acids, and the disaccharide trehalose, essential for the correct larval development and pupation. In conclusion, the present study demonstrates that milk industry byproducts can be upcycled as feed for TML, maintaining an optimal nutrient composition and favorably increasing the protein content.